Towards Cell free Therapy of Premature Ovarian Insufficiency: Human Bone Marrow Mesenchymal Stem Cells Secretome Enhances Angiogenesis in Human Ovarian Microvascular Endothelial Cells - Park, Hang-Soo (HSOA J Stem Cells Res Dev Ther, 2019)
Primary Ovarian Insufficiency (POI) refers to an ovarian loss of function in women under the age of 40. Unfortunately, currently, there is no effective treatment available for POI-related infertility. Alternatives such as the use of egg donations are culturally and ethically unacceptable to many couples. Human Bone marrow-derived Mesenchymal Stem Cells (MSCs) are known for their ability to differentiate into other cell types, once primed by the organ microenvironment. Importantly MSCs produce a vast array of bioactive factors many of them have been shown to enhance neovascularization in various tissues. Recently, preliminary data from our ongoing clinical trial revealed encouraging preliminary data after autologous MSC engraftment into the ovaries of 2 POI patients with durable elevation in serum estrogen levels and increase in size of treated ovaries sustained up to one-year post cell therapy. In this study, we investigated the action of the mechanisms of MSCs treatment on a POI ovary. We designed an in vitro study using MSC secretome and Human Ovarian Endothelial Cells (HOVECs) to understand the molecular mechanisms by which MSC mediates their angiogenic properties and regenerative effects. Human primary HOVECs were treatment with MSC secretome and examined by FACS for the expression of angiogenesis markers such as Endoglin, Tie-2, and VEGF. The formation of vessels was evaluated by using a 3D Matrigel tubulogenesis assay. We observed that the expression of proliferation marker Ki67 was significantly increased under treatment with MSC secretome in HOVEC cells (P4). MSCs secretome treatment also induced significantly higher expression of several angiogenic markers such as VEGFR2, Tie2/Tek, VE-Cadherin, Endoglin, and VEGF compared to matched control (P4). Furthermore, MSC secretome significantly increased the number of branching points in tubulogenesis assay (P4). Our study suggests that MSC secretome likely contains bioactive factors that can enhance ovarian angiogenesis. Further characterization of these factors can lead to novel therapeutic options for women with premature ovarian insufficiency and other related causes of female infertility.